Through and Through Mattress Suturing Versus Tie Over Dressing in Full Thickness Skin Graft Reconstruction. - مكية عدنان; فراس ملحم (Latakia University Journal -Medical Sciences Series, 2024)
Background: The successful acceptance of a skin graft by the wound bed hinges on direct contact to facilitate optimal nutrient diffusion. Immobilization of the graft is crucial in preventing seroma formation and rupture. Among the techniques employed for stabilization is through and through mattress suturing, which entails placing basic stitches on the graft’s surface and creating a cross stitch between the graft’s center and the recipient bed. This method enhances stability, adhesion, and ensures proper integration with the recipient bed. Aim: This study seeks to assess the efficacy of compression dressing compared to through and through mattress suturing in stabilizing full-thickness skin grafts concerning complete healing time and complication incidence. Materials and Methods: Following patient consent, thorough wound bed debridement was conducted, followed by full-thickness skin grafting and dressing application. Patients were randomized into two groups: one receiving a Tie-Over dressing after full-thickness skin grafting, and the other undergoing quilting sutures. The application of sutures, in terms of number and type, was tailored to individual tissue loss characteristics. Post-dressing application, patients underwent a follow-up on the fifth postoperative day to assess graft vitality. Subsequent follow-ups occurred one-month post-surgery to confirm graft success and detect complications. Results: The study encompassed 36 patients aged 19-63 years. Of these, 21 were male (58.3%) and 15 were female (41.7%). Surgical material loss was the primary cause for procedures in 16 patients, with the face and neck being the most frequent injury locations in 19 patients. The average material loss area for patients was 6.8 ± 0.5 cm2, and procedure duration ranged between 40-60 minutes. Graft failure within 5 days’ post-surgery was observed in 6 patients from the first group and 2 from the second group. However, after one month, graft failure occurred in 3 patients from the first group and 2 from the second group. The average healing time was 17.2 ± 2.8 days. Hospital stay averages were 5.9 days ± 1.2 for the first group and 5.1 days ± 0.9 for the second. Patients in the first group required dressing changes for an average of 15.2 days ± 2.7, whereas the second group averaged 9.7 days ± 3.2. Complications arose in 19 patients (52.8%) during the follow-up period. Conclusions: through and through mattress suturing streamlined surgical duration, reduced postoperative complications, minimized dressing changes, and shortened hospitalize time. This ultimately cut costs, enhancing convenience for both healthcare providers and patients. Hence, through and through mattress suturing are preferred for graft fixation.